Microleakage of pit and fissure sealings placed after enamel conditioning with phosphoric acid or with self‐etching primers/adhesives - Stefanie Amend; Roland Frankenberger; Christina Boutsiouki; Vanessa Scharrelmann; Julia Winter; Norbert Krämer (Wiley, 2021)
Abstract Background It is still not fully understood what pretreatment is best for achieving maximum tightness for pit and fissure sealings (PFS). Aim This study investigated microleakage of PFS placed after etching with phosphoric acid or after the application of self‐etching primers/adhesives (SEPA). Design 131 third molars were assigned to ten groups. In Hel‐P, Helioseal® was applied after phosphoric acid etching. In the other groups, SEPA were used (Dyr‐AP: Adper™ Prompt™ L‐Pop™, Dyract® Seal; Bea: BeautiSealant Primer and Paste; Hel‐Exp: Experimental primer, Helioseal®; Hel‐Cl: Clearfil™ SE Bond1, Helioseal®). Specimens were stored in distilled water at 37°C (28 days), followed by 3500 thermocycles and staining with 5% methylene blue (M) or 5% silver nitrate (S). After methylene blue staining and sectioning, microleakage was assessed light microscopically. During silver nitrate staining, specimens were dissolved by 32% HCl and remaining PFS were evaluated under a SEM. Results Tightness, percentage of penetrated area, and maximum dye penetration were best for Hel‐P and Hel‐Cl (p < 0.05). Conclusions Phosphoric acid etching of enamel and Clearfil™ SE Bond resulted in the best sealing quality. Methylene blue staining allowed the evaluation of more criteria (fissure shape, voids, sealant penetration depth) compared to silver nitrate.